Quality Evaluation of Yogurt Produced from Chili Pepper-Derived Starter Culture - EZEALOR, Mordecai C.; ORHEVBA, Bosede A.; OYEBAMIJI, Ruth O. (FUDMA Journal of Engineering and Technology, 2026)
The study investigated the production of yogurt using starter cultures developed from chili pepper and evaluated its effect on some quality parameters of the resultant yogurt. The quality parameters investigated were: nutritional content and sensory attributes. Statistical analysis, (ANOVA) and Duncan’s multiple range test were applied to assess significant differences. The results revealed that the addition of chili pepper have significant effects (p<0.05) on yogurt quality parameters. Moisture content ranged from 83.46±0.15% to 89.50±0.20%, crude protein from 3.15±0.55% to 6.01±0.11%, crude fat from 2.86±0.15% to 5.89±0.09%, and ash content from 0.50±0.01% to 0.69±0.025%. Vitamin A levels ranged from 0.07% to 0.20%, indicating that chili pepper enhanced the Vitamin A content compared to the control (0.06%). Calcium content varied between 284 mg/100g and 342 mg/100g, while potassium content ranged from 92.32 mg/100g to 172.11 mg/100g. Sensory attributes varied significantly with the taste quality range from 3.00±0.50 to 5.00±0.50, texture from 4.00±0.50 to 5.00±0.50, aroma from 2.00±0.50 to 4.00±0.50, appearance from 2.17±0.29 to 5.00±0.50, and general acceptability from 3.00±1.00 to 5.00±0.50. In conclusion, chili pepper shows promising results for use in starter culture for yogurt production, because it can positively influence the nutritional and sensory properties of the yogurt, compared to the control.